IMPROVING LEARNING QUALITY AND STUDENT NUMERACY THROUGH DATA DRIVEN PLANNING AT SMAIT MA'HAD RABBANI - Putra, Wahyudi; Syamsir, Syamsir; Sujirman, Sujirman; Asha, Lukman; Warlizasusi, Jumira (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to improve the quality of learning and numeracy skills of students through the implementation of data-based planning at SMAIT Ma'had Rabbani Central Bengkulu. This study uses an action research design by referring to a framework consisting of four main steps, namely Identification, Reflection, Improve Planning, and Improve Implementation. This data-driven planning strategy is designed to support more effective decision-making in an effort to improve academic performance. The results showed significant improvements in various indicators. The quality of learning increased by 11.97% compared to 2023, with the achievement reaching 68.69 in 2024. Student numeracy also recorded a remarkable improvement of 50.88%, with the score reaching 86.36 in 2024, making it the best indicator.